FAKTOR DETERMINAN NILAI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Zumrotun Nafiah; Wachidah Fauziyanti (JURNAL STIE SEMARANG, 2022)
The increase in the value of the company is usually measured by the increase in the stock market price. The stock market price is formed through the mechanism of supply and demand in the capital market. The purpose of the study was to determine the Return On Assets, Dividend Payout Ratio, Debt to Equity Ratio effect on firm value in manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017, totaling 149 companies. To achieve the research objectives, the data that has been collected was analyzed using the multiple regression analysis method. This multiple regression analysis method serves to predict changes in the Y variable which is influenced by the X variable. The results of the study Return On Assets a significance value of 0.000 <0.05, it can be concluded that Return On Assets has an effect on Price To Book Value. Dividend Payout Ratio: a significance value of 0.294 > 0.05, it can be concluded that the Dividend Payout Ratio has no effect on Price to Book Value. Debt to Equity Ratio: a significance value of 0.144 > 0.05, it can be concluded that the Debt to Equity Ratio has no effect on Price to Book Value.